Field (In)dependence Flexibility Following a Virtual Immersion Is Associated With Cybersickness and Sense of Presence - Maneuvrier, A.; Decker, L. M.; Renaud, P.; Ceyte, G.; Ceyte, H. (Frontiers in Virtual Reality, 2021)
Field dependence-independence (FDI) is a psychological construct determining an individual’s approach of the perception-cognition coupling. In VR context, several studies suggest that an individual’s perceptive style is susceptible to shift towards a more FI mode through down-weighting of conflicting visual cues. The present study proposes to investigate the potential flexible nature of FDI following a virtual immersion and to assess if this flexibility might be associated with the subjective experience of VR. 86 participants explored a real world-like virtual environment of approximately 10 minutes. FDI levels were measured before and after the VR exposure using the Rod and Frame Test. Their subjective experience of VR was measured a posteriori (cybersickness, sense of presence) and used in order to build two experimental groups via a cluster analysis. Results showed that only participants with a poor subjective experience of VR (i.e. a low level of sense of presence associated with a high level of cybersickness) significantly shifted to a more FI mode, which is discussed as a sensory re-weighting mechanism. Pragmatical applications are discussed, and future studies are outlined, based on the conclusion that FDI might be more flexible than we thought, which could shed light on the psycho-physiology of VR.